Diverse Dwellings "on" and "in" Mystery - Gardner, Morgan K.; Mandoki, Monika Judith (Journal of the Canadian Association for Curriculum Studies, 2025)
Practitioner self-study narratives play an important role in the engagement of Mystery, particularly in neoliberal educational contexts, which tend to prioritize rational goal-settings and answers as compared to Mystery’s a-rational ways of knowing (i.e., ways beyond rational knowledge) that dwell in our Being. As two educators, we share our curricular and pedagogical dwellings “on” and “in” Mystery. This inquiry stems from our desire to create generative curricular spaces for students to explore Mystery within their Being, with the Whole of existence, and with respect to their interconnectivity to global-local contexts and currents of struggle. The study’s three thematic findings are communicated via a multi-voiced text of narrative, poetic and academic writing. First, we lament the insufficient engagement of Mystery in education, while coming to know the strengths of such lament for transformative educational work. Second, we narrate our diverse dwellings “on” Mystery, which articulate our understandings and practices of Mystery. Third, we explore the value of an existential-ontology of education as a means to enhance engagement in Mystery with students, within the complexity of their whole selves and the Whole of life.